Pengalihan Aset Jaminan Fidusia Saat Proses Penyidikan Di Kepolisian - Agus Setiyawan; Sri Astutik; Moh. Taufik (JOURNAL OF SHARIA ECONOMICS, 2022)
The use of fiduciary security as a proprietary security right plays a crucial role in supporting financing activities and maintaining economic stability. However, in practice, problems frequently arise in the form of the transfer of fiduciary collateral assets by debtors without the prior written consent of creditors, which may result in criminal legal consequences. This article aims to analyze the legal framework and law enforcement practices concerning the transfer of fiduciary collateral assets during police investigation processes. This study employs a normative juridical research method with statutory and conceptual approaches. The findings indicate that Law Number 42 of 1999 on Fiduciary Security provides a clear legal basis regarding the prohibition of transferring fiduciary objects and the imposition of criminal sanctions on violators. In the context of investigations, the police play a strategic role in uncovering fiduciary transfer offenses, while simultaneously facing challenges in balancing criminal law enforcement with the protection of creditors’ civil rights. Therefore, a proportional law enforcement approach, including the application of restorative justice, is necessary to achieve legal certainty, justice, and expediency in resolving fiduciary cases.